ПИТАННЯ ЧИСЕЛЬНОСТІ ХРАМІВ СЛОВíЯНСЬКОЇ ТА ХЕРСОНСЬКОЇ ЄПАРХІЙ В ІСТОРІОГРАФІЇ ТА ДЖЕРЕЛАХ (Zaporizhzhia Historical Review, 2021)
The issue of the number of orthodox churches in Slavonic and Cherson diocese after the liquidation of Zaporizhya Sich is investigated on the basis of the original archive sources and published results of researches. Various mistakes in traditional historiography are criticized.